Pelatihan Pengolahan Jantung Pisang Sebagai Alternatif Makanan Nabati (Stik Daging) Untuk Meningkatkan Ekonomi Masyarakat Desa Tutulo Kecamatan Botumoito Kabupaten Boalemo - Abdjul, Tirtawaty; Nurhayati, Nurhayati (Universitas Negeri Gorontalo, 2024)
The aim of the activity training is to increase community understanding regarding making meat sticks from banana blossoms and improve the economy of the community in Tutulo Village, Botumoito District, Boalemo Regency. The method of implementing activities is carried out using observation, interviews, training, and mentoring. The approach used in this activity uses an active participatory approach, where training is provided in four stages: planning, preparation, implementation, and evaluation. The results of the activity showed that the public gained more understanding about innovations in processing banana blossoms into sticks that resemble meat. Organoleptic tests on imitation meat stick products made from banana blossoms showed positive acceptance from respondents, both in terms of color, aroma, taste, and texture. This product is considered to have an attractive color, an appetizing aroma, a taste similar to imitation meat, and a texture that meets consumer expectations. Overall, these imitation meat sticks have the potential to be accepted as a quality and satisfying plant-based food alternative.